2023
DOI: 10.1021/jacs.2c08000
|View full text |Cite
|
Sign up to set email alerts
|

Vanadium-Catalyzed Dinitrogen Reduction to Ammonia via a [V]═NNH2 Intermediate

Abstract: The catalytic transformation of N 2 to NH 3 by transition metal complexes is of great interest and importance but has remained a challenge to date. Despite the essential role of vanadium in biological N 2 fixation, welldefined vanadium complexes that can catalyze the conversion of N 2 to NH 3 are scarce. In particular, a V(N x H y ) intermediate derived from proton/electron transfer reactions of coordinated N 2 remains unknown. Here, we report a dinitrogen-bridged divanadium complex bearing POCOP (2,6-( t Bu 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 101 publications
0
7
0
Order By: Relevance
“…This could be justified with respect to a very recent report by Huang et al that experimentally and theoretically suggested that the NRR on V active sites could energetically prefer a distal pathway negating the chances of the formation of hydrazine, rightly corroborating our experimental results. 48 Thus, the NRR on our active material of VO 2 @CN was kinetically facilitated yielding 0.31 and 0.52 μmol h −1 mg cat −1 of NH 3 in Na 2 SO 4 and HCl, respectively. The concentrations of ammonia in all cases were calculated using the standard calibration curves and the corresponding linear regression plot in the relevant acidic or neutral electrolytes (Fig.…”
Section: Synthesis and Structural Characterizationmentioning
confidence: 76%
“…This could be justified with respect to a very recent report by Huang et al that experimentally and theoretically suggested that the NRR on V active sites could energetically prefer a distal pathway negating the chances of the formation of hydrazine, rightly corroborating our experimental results. 48 Thus, the NRR on our active material of VO 2 @CN was kinetically facilitated yielding 0.31 and 0.52 μmol h −1 mg cat −1 of NH 3 in Na 2 SO 4 and HCl, respectively. The concentrations of ammonia in all cases were calculated using the standard calibration curves and the corresponding linear regression plot in the relevant acidic or neutral electrolytes (Fig.…”
Section: Synthesis and Structural Characterizationmentioning
confidence: 76%
“…Only one molecular electrocatalyst (tri (phosphine) borane iron system) has been reported to reliably proved the reaction mechanism, but it needs a lower temperature (−35°C) to slow down the background HER and high reduction potential 193 . Huang et al 194 first separated and characterized the neutral hydrazide complex intermediate ([V]═NNH 2 ) in the vanadium metal complexes catalyzed NRR system. Dinitrogen compounds and NH 3 were obtained by the reduction of protonation by vanadium amino complexes ([V]–NH 2 ).…”
Section: Nitrogen Activation Via Mediatorsmentioning
confidence: 99%
“…The research on N 2 reduction reactions (N 2 RRs) in molecular systems dates back to the 1960s, and ever since seminal work was published by Chatt, Hidai, and co-workers, tremendous efforts have been invested in the development of efficient catalysts for the synthesis of nitrogen-containing molecules directly from N 2 . Metal dinitrogen complexes necessarily feature strong π-backdonation from electron-rich metal centers to N 2 π* orbitals; therefore, the following N 2 functionalization is almost invariably realized by electrophilic attacks of metal N 2 complexes with potent electrophiles, such as H + , C + , and Si + , leading to diazenido and/or hydrazido complexes (Figure ). More important is that such processes initiate the vast majority of catalytic N 2 RRs .…”
Section: Introductionmentioning
confidence: 99%